Kemampuan pemacahan masalah matematis menggunakan model carousel feedback - Salamah, Zalfaurrifdah Noo; Juariah; Rachmawati, Tika Karlina (Papanda Publisher, 2025)
The background of this research is based on the results of a preliminary study and interviews with mathematics teachers at one of Bandung's public junior high schools where students' mathematical problem-solving abilities still need to be improved. This study aims to determine the difference in improvement between the mathematical problem-solving abilities of students who use the Carousel Feedback model and those who use the conventional model. This type of research is a quasi-experimental study. The population in this study were all students of class VIII. The sample in the study was taken from 2 classes using random sampling techniques, namely VIII C as the experimental class with 32 students, and class VIII B as the control class with 32 students. The data collection technique used a test device. The data analysis technique used a two-average test. If is normally distributed and has a homogeneous variance, it is continued with an independent t-test. This study concluded that there is a difference in the improvement of mathematical problem-solving abilities of students who use the Carousel Feedback Learning Model with students who use the conventional learning model because the value is greater than the value. So is rejected, meaning there is a difference in the increase in mathematical problem-solving abilities between students who use Carousel Feedback learning and students who use conventional learning